1970
DOI: 10.1161/01.str.1.6.454
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disease: Frequency and Population Selectivity in an Upper Midwestern Community

Abstract: The number of new strokes diagnosed in the communities of Fargo, North Dakota, and Moorhead, Minnesota, was determined by intensive review of medical records in all hospitals, clinics and nursing homes in the area for the period 1965 to 1966. These two adjacent communities have unusual advantages for such a study because their neurological diagnostic facilities are of excellent quality, the population served is stable, and the communities are isolated from other medical facilities by many miles. Out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The age distribution for each type of stroke and all types considered together was similar to age distributions of stroke patients in the upper Midwest. 6 The risk of stroke among Mexican men and women was essentially equal as has been found in other populations. 5 " 8 Hypertension, cardiac disease and diabetes mellitus are commonly cited as predisposing illnesses in stroke patients in the United States and the same predisposing conditions emerged as common in the Mexican population.…”
Section: Figurementioning
confidence: 63%
“…The age distribution for each type of stroke and all types considered together was similar to age distributions of stroke patients in the upper Midwest. 6 The risk of stroke among Mexican men and women was essentially equal as has been found in other populations. 5 " 8 Hypertension, cardiac disease and diabetes mellitus are commonly cited as predisposing illnesses in stroke patients in the United States and the same predisposing conditions emerged as common in the Mexican population.…”
Section: Figurementioning
confidence: 63%
“…10 In the present experiments a novel model of vascular hypersensitivity to noradrenaline was used to amplify any possible inherent action of the sympathetic nerves on the cerebral vessels. We have previously shown that in obstructive jaundice there is an altered renal vascular sensitivity to infused noradrenaline both in vivo 11 and in vitro. 12 This was postulated to be due to some factor in the jaundiced plasma which was capable of sensitizing both renal and femoral arteries to the pressor effects of noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…The model's goodness of fit was evaluated by F test for the overall model and the R 2 value. The single harmonic regression equation for the frequency of occurrence of strokes or TIA is y, = /x + j8,sin(277 t/12) + /8 2 cos(27r t/12) (1) where /x is the mean monthly frequency of stroke or TIA, t is month 1,2, 3 18, and y, is the predicted number of stroke/TIA cases for month t. This is the general representation for a function with a 12-month periodicity and a single peak and trough. It is possible that the pattern is more complicated.…”
Section: Methodsmentioning
confidence: 99%